Understanding earthquake potential for future hazard mitigation - Triyoso, Wahyu; Kongko, Widjo; Prasetya, Gegar S. (Frontiers in Built Environment, 2025)
This study re-examines a broad region of the Sumatran subduction zone and off-coast southern West Java, building on findings of relative quiescence and utilizing the modified probability gain (mG) concept. By comparing pre- and post-quiescence seismicity, we identify potential earthquake sources and assess associated tsunami hazards. We propose a novel combined model integrating normalized seismicity smoothing, geodetic moment rate, and mG to characterize earthquake likelihood better. This model, coupled with a robust seismicity rate model, enables a spatiotemporal earthquake potential hierarchy for refined seismic hazard assessment. Our results confirm prior quiescence findings in specific zones and identify novel potential source regions for significant future earthquakes. We estimate tsunami height, emphasizing the importance of multiple source areas and static stress loading. By examining pre- and post-event expectations, we aim to improve understanding of major earthquakes in the Sumatran Subduction Zone and inform disaster mitigation strategies. This study provides crucial insights for enhanced regional earthquake and tsunami preparedness.